(untitled) (Scientific journal of the Fergana State University, 2025)
This article analyzes the lexical-semantic concepts of "friendship" and "enmity" in Uzbek and English. The study examines the etymological origin of the main nominative lexemes expressing these concepts - "friend/enemy", their synonymous and antonymic series, and their location within the semantic field.